Public Service Media versus Digital Media Platforms: A Threat or an Opportunity? - Vysloužilová, Kristýna (Communication Today, 2025)
Public service media (PSM) are continually facing challenges on many fronts; one of them is the expansion of digital media platforms and new technologies in general. Based on the current scholarly literature, digital media are generally perceived either as a threat to PSM legitimacy or as an opportunity to support their social value by engaging their audiences more effectively. The study focuses on the potential of digital media as of a tool enhancing audience participation. It presents results of a pilot quantitative research on a representative sample of Czech population (N = 1,500), mapping the frequency in usage and trust respondents have in various information sources. Also, it analyses the perception of selected representatives of PSM and digital media platforms, particularly the Czech Television and Facebook, which were analysed in terms of their general perception, perception of their content, and engagement potential. The aim of the study is to identify strengths and weaknesses of digital media platforms compared to PSM to map their engaging potential. The author also analyses some significant differences among various socio-demographic groups, which indicate that PSM should pay special attention to audience segments especially according to their age and level of education.